The strategy for mitigating risk in sharia hotels based on the DSN-MUI Fatwa regarding the service and restaurant operational aspects - Dwila Sempi Yusiani; Elisa Kusrini; Eley Suzana Kasim (Faculty of Economics, Universitas Islam Indonesia, 2023)
Purpose – The study aims to develop a risk mitigation approach based on the operational aspects of services and restaurants in sharia hotels.Methodology – A series of semi structured interviews was conducted with various relevant participants consisting of lecturers and Indonesian Ulema Council (MUI) employees. The interviews aimed to elicit information pertaining to the identification of risks and risk handling priorities in halal certification sharia hotels.Findings – In general, risk identification and risk handling were proposed to provide recommendation to sharia hotels in mitigating risks to obtain halal certificate. The findings indicate that numerous risk factors made it difficult for hotels to obtain halal certification. Therefore, the hotel needs to know potential hazards in their operational activities of the given services so that appropriate risk mitigation can be implemented.Implications – This study's findings can be applied to improve research in the field of sharia hotels, specifically certification and implementation criteria. With the exact terms and circumstances of each criterion, it will be easier for the hotel to prepare to become a sharia hotel that adheres to Islamic sharia principles, particularly in growing halal tourism in various regions of Indonesia.Originality – This research contributes significantly to the area of halal tourism. In addition, this paper investigates risk analysis based on Indonesian regulations that are hardly ever discussed. Therefore, the findings of this study can assist hotel management, sharia tourism practitioners, and policymakers with relatively new information.